2020
DOI: 10.1212/wnl.0000000000010884
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of remote ischemic postconditioning after thrombolysis in patients with stroke

Abstract: Objective:To determine the effect of remote ischemic post-conditioning (RIPC) on acute ischemic stroke (AIS) patients undergoing intravenous thrombolysis (IVT).Methods:A single-center, randomized controlled trial was performed with AIS patients receiving IVT. Patients in the RIPC group were administered RIPC treatment (after IVT) during hospitalization. The primary endpoint was a score of 0 or 1 on the modified Rankin scale (mRS) at day 90. The safety, tolerability and neuroprotection biomarkers associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…The interest of RIC in AIS has emerged in the last years. Three clinical trials have evaluated different strategies of RIC among AIS with mixed results 13 15 . In parallel, several clinical trials are now ongoing to investigate the efficacy of RIC in patients with acute stroke 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The interest of RIC in AIS has emerged in the last years. Three clinical trials have evaluated different strategies of RIC among AIS with mixed results 13 15 . In parallel, several clinical trials are now ongoing to investigate the efficacy of RIC in patients with acute stroke 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Four trials investigated the use of rPerc in stroke patients receiving reperfusion therapy: two combining rPerc with IVT, and two trials also treating patients with EVT (see paragraph on neuroprotection and EVT). In 2020 a single center trial ( n = 68) reported significant results in a trial of rPerc in which patients with AIS were treated with IVT and subsequent ischemic perconditioning ( 37 ). Excellent recovery (mRS 0–1) at 3 months was obtained in 72% of patients in the rPerc group vs. 50% in controls (adjusted risk ratio, 9.85; 95%CI, 1.5 to 63.2), though patients with severe stroke (NIHSS >24) were excluded from this trial.…”
Section: Studies Combining Neuroprotection and Ivtmentioning
confidence: 99%
“…Концепция дистанционного посткондиционирования предполагает более слабое, но более простое в осуществлении воздействие. Локальная ишемия в другом органе (обычноконечности) приводит к образованию цитокинов и паракринных агентов, которые с кровотоком могут попасть в другие органы и увеличить их устойчивость к повреждающим воздействиям [143][144][145]. Обычно такие эффекты имеют небольшую амплитуду, и в настоящее время этот подход также не нашел широкого применения в клинической практике.…”
Section: свободные радикалы при ишемическом повреждении мозгаunclassified